Palmatine alleviates hyperalgesia by inhibiting the expression of calcitonin gene-related peptide in the trigeminal ganglion of rats with chronic constriction injury of the infraorbital nerve. Issue 4 (May 2020) - He, L.; Liu, L.; Guan, S.; Zheng, X.; Ge, H.; Yin, C.; Shen, Y.; Tan, M.; Wang, C.; Gao, Y.; Xiong, W.
Abstract: Trigeminal neuralgia is one of the most common of the neuropathic pains, and it can seriously influence patients' quality of life. Calcitonin gene-related peptide (CGRP) is a type of nociceptive neurotransmitter that is expressed in neurons of the trigeminal ganglion and plays a major part in transmitting pain. The rat model of trigeminal neuralgia was established by causing a chronic constriction injury of the infraorbital nerve (CCI-ION). Male Sprague-Dawley rats (n = 24) were randomly divided into a sham control group (sham, n = 6), sham-treated with palmatine group (sham + palmatine, n = 6), trigeminal nerve model group (TN, n = 6), and trigeminal nerve treated with palmatine group (TN + palmatine, n = 6). Fifteen days after the operation the mechanical response threshold was decreased in the TN group compared with the sham group. From postoperative day 7 to day 15, the mechanical response threshold in the TN + palmatine group significantly increased compared with the TN group. On postoperative day 15 the results of quantitative polymerase chain reaction (qPCR), immunohistochemical staining, and western blotting showed an obvious increase in expression of CGRP and its receptors, serum concentrations of interleukin-1β (IL-1β), and tumour necrosis factor-α (TNF-α), and phosphorylation of protein kinase C (PKC) in the trigeminal ganglia of the TN group compared with the sham group, but these increases could be down-regulated by treatment with palmatine. Palmatine might therefore have therapeutic potential for the treatment of trigeminal neuralgia by inhibiting the expression of CGRP and its receptors in trigeminal ganglia, suppressing the serum concentrations of IL-1β and TNF-α, and decreasing the phosphorylation of PKC in the trigeminal ganglia of affected rats.